2007
DOI: 10.1111/j.1745-3992.2007.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Do Proper Accommodation Assignments Make a Difference? Examining the Impact of Improved Decision Making on Scores for English Language Learners

Abstract: Does it matter if students are appropriately assigned to test accommodations? Using a randomized method, this study found that individual students assigned accommodations keyed to their particular needs were significantly more efficacious for English language learners (ELLs) and that little difference was reported between students receiving incomplete or not recommended accommodations and no accommodations whatsoever. A sample of third and fourth grade ELLs in South Carolina (N = 272) were randomly assigned to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 10 publications
2
74
2
Order By: Relevance
“…Our results conflict with some existing research, which have sometimes found positive results across grades and subjects (Abedi, 2009;Kopriva et al, 2007). However, these studies that have found positive results for accommodations that include pop-up glossaries have had few students in the glossary accommodation condition and were not designed to study pop-up glossaries per se.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Our results conflict with some existing research, which have sometimes found positive results across grades and subjects (Abedi, 2009;Kopriva et al, 2007). However, these studies that have found positive results for accommodations that include pop-up glossaries have had few students in the glossary accommodation condition and were not designed to study pop-up glossaries per se.…”
Section: Discussioncontrasting
confidence: 56%
“…Because there were several, co-occurring accommodations in the "computerized accommodation" condition, it is unclear whether the pop-up glossary produced the benefit that ELs experienced. Furthermore, Kopriva et al (2007) were primarily focused not on specific accommodations, but rather how ELs' individual differences in educational needs affected their accommodation preferences. When researchers compared test results with recommendation results, they found a significant effect for the pop-up glossaries only when the students were recommended for that accommodation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have expressed concerns about the impact of such accommodations for ELL students in large-scale assessments; that is, some accommodations appear to be are more appropriate than others for ELL students (e.g., Abedi & Gándara, 2006;Abedi, Hofstetter, & Lord, 2004;Abedi, Lord, Hofstetter, & Baker, 2000;Kopriva, Emick, Hipolito-Delgado, & Cameron, 2007) although the studies yielded inconclusive findings. In addition to accommodations, it is also important to take various student characteristics into account while examining school achievement of ELL students with and without disabilities (e.g., Abedi et al, 2000;Abedi et al, 2004).…”
Section: Accommodations For English Language Learnersmentioning
confidence: 99%
“…States gradually began to more carefully guide the assignment of accommodations according to students' proficiency levels in English, academic literacy in English and their native language, prior schooling, and content instruction in their native language, using guidance from Acosta et al (2008) and Kopriva, Emick, Hipolito-Delgado, and Cameron (2007). Indeed, Kopriva et al found that when MLLs were assigned accommodations that matched their linguistic and cultural needs during testing, they were better able to show what they knew than MLLs who were assigned incomplete accommodations (i.e., assigned accommodations without matching them to more linguistically responsive criteria) and MLLs who were not assigned any accommodations at all.…”
Section: First Wave Of Changesmentioning
confidence: 99%